A high-frequency half-bridge driving circuit topology for HID lamps. (October 2016) - Pan, Y; Lin, J; Su, S; Shih, T-M
A half-bridge circuit topology for driving high-intensity discharge lamps at high frequencies is proposed. The high-frequency square wave is modulated synchronously by low-frequency, sawtooth signals. Under such circumstances, the phenomenon of acoustic resonance can be successfully prevented because standing waves within the wall of the lamp are eliminated. This has been experimentally verified. Results obtained will offer useful information for designing high-efficiency high-intensity discharge lamps.